Noncovalent pi-stacked robust topological organic framework - YAVUZ, İLHAN (NATL ACAD SCIENCES, 2020)
Organic frameworks (OFs) offer a novel strategy for assembling organic semiconductors into robust networks that facilitate transport, especially the covalent organic frameworks (COFs). However, poor electrical conductivity through covalent bonds and insolubility of COFs limit their practical applications in organic electronics. It is known that the two-dimensional intralayer pi center dot center dot center dot pi transfer dominates transport in organic semiconductors. However, because of extremely labile inherent features of noncovalent pi center dot center dot center dot pi interaction, direct construction of robust frameworks via noncovalent pi center dot center dot center dot pi interaction is a difficult task. Toward this goal, we report a robust noncovalent pi center dot center dot center dot pi interaction-stacked organic framework, namely pi OF, consisting of a permanent three-dimensional porous structure that is held together by pure intralayer noncovalent pi center dot center dot center dot pi interactions. The elaborate porous structure, with a 1.69-nm supramaximal micropore, is composed of fully conjugated rigid aromatic tetragonal-disphenoid-shaped molecules with four identical platforms. pi OF shows excellent thermostability and high recyclability and exhibits self-healing properties by which the parent porosity is recovered upon solvent annealing at room temperature. Taking advantage of the long-range pi center dot center dot center dot pi interaction, we demonstrate remarkable transport properties of pi OF in an organic-field-effect transistor, and the mobility displays relative superiority over the traditional COFs. These promising results position pi OF in a direction toward porous and yet conductive materials for high-performance organic electronics.
Keywords: COFs; field-effect transistor; organic conductor; HIGH-PERFORMANCE; CRYSTALLINE; CHEMISTRY